2020
DOI: 10.3390/molecules25143164
|View full text |Cite
|
Sign up to set email alerts
|

10-Gingerol Targets Lipid Rafts Associated PI3K/Akt Signaling in Radio-Resistant Triple Negative Breast Cancer Cells

Abstract: 10-gingerol is a major phenolic lipid found in the rhizomes of ginger (Zingiber officinale). Being amphiphilic in nature, phenolic lipids have the ability to incorporate into cell membranes and modulate membrane properties. The purpose of the present study was to evaluate the effects of 10-gingerol on lipid raft/membrane raft modulation in radio-resistant triple negative breast cancer (MDA-MB-231/IR) cells. The effects of 10-gingerol on MDA-MB-231/IR cells’ proliferation, clonogenic growth, migration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Moreover, [10]-Gingerol has been reported to exhibit anti-tumor activity by inducing apoptosis through the MAPK pathway in HCT116 human colon cancer cells (18). Gingerol has been subsequently shown to induce apoptosis in a variety of cancer cell types (17,(28)(29)(30). In this study, [10]-Gingerol induced apoptosis by activating the caspasefamily proteins (Caspase-3, Caspase-7, and Caspase-8).…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, [10]-Gingerol has been reported to exhibit anti-tumor activity by inducing apoptosis through the MAPK pathway in HCT116 human colon cancer cells (18). Gingerol has been subsequently shown to induce apoptosis in a variety of cancer cell types (17,(28)(29)(30). In this study, [10]-Gingerol induced apoptosis by activating the caspasefamily proteins (Caspase-3, Caspase-7, and Caspase-8).…”
Section: Discussionmentioning
confidence: 72%
“…Recently, 10-gingerol (C 21 H 34 O 4 ), a β-hydroxy ketone and a phenolic member of monomethoxybenzene, was found to modulate the lipid rafts of breast cancer MDA-MB-231/IR cells. It caused the redistribution of cholesterol content of the lipid rafts and rafts and attenuated the key PI3K/Akt signaling components in lipid rafts of cells ( Ediriweera et al, 2020 ). Another gingerol derivative (6-gingerol) was shown to modulate a variety of classical signaling cascades in different types of cancers especially ERK, JNK, PI3-K/Akt, PLC-γ1, and JAK/STAT pathways ( de Lima et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PTEN deficiency is one of the most common types of aberrations in cancer, and its effect is particularly significant in glioblastoma and prostate cancer. 59 Ediriweera et al 60 showed that 10‐gingerol, a natural phenolic lipid, can bind to cell membranes and regulate membrane properties and thus affect the PI3K/Akt signalling pathway in radiation‐resistant triple‐negative breast cancer (MDA‐MB‐231‐IR) cells by regulating lipid raft formation, thereby inhibiting the proliferation, migration and invasion of cancer cells and inducing apoptosis. This process is mainly caused by the entry of amphiphilic 10‐gingerol into the plasma membrane of cancer cells and the transfer of caveolin from the lipid raft to the membrane outside the lipid raft, destroying the lipid raft.…”
Section: Lipid Rafts In the Pi3k/akt Signalling Pathwaymentioning
confidence: 99%